PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, KOMPETENSI SUMBER DAYA MANUSIA, DAN PENERAPANSISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Indragiri Hulu) - Ma’ari Bagus; Rasuli M; A Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to test: The effect of the application of government accountingstandards, the application of regional financial accounting systems, competency ofhuman resources, and the application of government internal control systems to thequality of financial statements. The population in this study is all apparatus in 27Indragiri Hulu Regency OPD. In this study the sample used amounted to 81 respondents,who were selected using the purposive sampling method. This study uses primary data bydistributing questionnaires. The analytical method used in this study is multiple linearregression analysis. The analytical tool used in this study is Statistical Product andService Solution (SPSS) version 21. The results of this study indicate that: 1) theapplication of government accounting standards affects the quality of financialstatements with a significant level of 0.003, 2) the application of regional financialaccounting systems affect the quality of financial statements with a significant level of0.019, 3) competency of human resources affect the quality of financial statements with asignificant level of 0.033, and 4) the application of government internal control systemsaffect the quality of financial statements with a significant level of 0.006.Keywords: Application of Government Accounting Standards, Implementation ofRegional Financial Accounting Systems, Competence of Human Resources,Application of the Government Internal Control Systems, Quality ofFinancial Statements.